Motivation And Teaching Experience: Does Teaching Experience Affect Lecturers’ Motivation In Teaching Online? (Sains Humanika, 2018)
There are a few challenges for all lecturers to apply online teaching practices. Among the problems are preparing teaching materials for online learning and lack of motivation in teaching and learning using online tools. This study intends to determine whether teaching experience affect lecturers’ motivation in teaching online. The respondents consist of 149 lecturers from Jabatan Matematik dan Sains Komputer (JMSK) with different subject matter expertise. Teaching experience was assessed using a multiple choice question in demographics and the lecturer’s motivation was measured using four primary dimensions i.e., ease of use (EOU), usefulness (USE), enjoyment (E), and self-confidence (SC). In order to measure these four dimensions, measurement items were adapted from previous researchers. The Wilk’s Lambda within the Multivariate Tests shows the significance (p-value) is more than 0.05, which means that the lecturer’s motivation is not significantly affected by their prior experience. Study also found that most of the lecturers in the polytechnics have between 4-6 years of teaching experience with the highest percentage of 34.2% and only one new lecturer with experience lower than one year was involved in this survey (0.7%). To conclude, these findings indicated that teaching experience does not affect a lecturer’s motivation in using online tools. Equally important, the application of appropriate teaching and learning tools makes the teaching and learning more effective in the classroom. Aided teaching techniques with several Web 2.0 applications also helped lecturers to diversify their teaching styles. It is hoped that the benefits from this study would be able to help the lecturers to be aware of the potential of their creativity and to be able to practice this in their teaching, as well as in recognizing the importance of the factors that motivate the creativity of lecturers in teaching online. This study formerly looked at the factors that motivated the lecturers in using online tools and highlighted three main factors that can affect a lecturer’s motivation which are (i) knowledge; (ii) perceptions, and (iii) skills.
Keywords: Intrinsik; ekstrinsik; motivasi; e-pembelajaran; politeknik; pengajaran dan pembelajaran; pendidikan